On Slant Magnetic Curves in S-manifolds. Issue 4 (2nd October 2019) - Güvenç, Şaban; Özgür, Cihan
Abstract : We consider slant normal magnetic curves in (2 n + 1)-dimensional S -manifolds. We prove that γ is a slant normal magnetic curve in an S -manifold ( M 2 m + s, φ, ξ α, η α, g ) if and only if it belongs to a list of slant φ -curves satisfying some special curvature equations. This list consists of some specific geodesics, slant circles, Legendre and slant helices of order 3. We construct slant normal magnetic curves in ℝ 2 n + s (–3 s ) and give the parametric equations of these curves.